(untitled) (Research, Society and Development, 2026)
Autism Spectrum Disorder (ASD) is a group of neurodevelopmental disorders characterized by specific delays and deviations in social, communicative, and cognitive development. It is primarily defined by impairments in speech, social interactions, and repetitive behaviors. One of the daily activities affected by autism is oral hygiene, which is challenging due to sensory and behavioral alterations. The objective of this study was to review the literature on the most common oral health conditions in individuals with ASD and how these conditions influence dental treatment. An advanced search was conducted in the PubMed database using the Boolean operator "AND" and the keywords: "Autism Spectrum Disorder" and "oral health." As a result, 15 articles met the established eligibility criteria. Based on the findings, it can be concluded that individuals with ASD are more prone to poor oral health, primarily due to delays in seeking dental care. This delay is attributed to factors such as limited access to specialized professionals, caregivers prioritizing other health concerns over oral health, and the patients’ lack of cooperation during dental visits. Consequently, individuals with ASD exhibit higher rates of cavities, gingivitis, and parafunctional habits, leading to the need for more extensive and invasive dental treatments, which may require sedation or general anesthesia—an expensive procedure associated with certain risks. Therefore, studies emphasize the importance of early dental care to mitigate these issues.